NEGATIVE PRESSURE OF STRETCHED LIQUID WATER. GEOCHEMISTRY OF SOIL CAPILLARIES - Mercury L.; Tardy Y. (My University, 2001)
Solution-mineral equilibria in the unsaturated zone above aquifers requires us to take into account the negative internal pressure of liquid water, distributed in fine pores of a partially filled medium. The proposed method affords calculation of the thermodynamic properties of capillary water by extrapolating their dependencies measured at positive pressures, into a negative pressure domain, finding supports from measurements already obtained on the stretched water. Besides Gibbs free energy, enthalpy, entropy, heat capacity, isobaric expansibility and isothermal compressibility of soil water, calculations of the dielectric constant, the water-air interfacial tension and the pH at neutrality have been established. This thermodynamic characterization of the water state in soils enables us to consider quantitatively the melting and boiling temperatures in soils or in fluid inclusions, the corresponding latent heat, or the lowering of the saturated vapour pressure in the unsaturated zone of weathering profiles. This pressure approach implies some reviewed consequences about solute species, gases and mineral solubilities, or still hydration-dehydration phenomena, in capillaries.